(untitled) (Swiss Medical Weekly, 2010)
Kras, a small intracellular GTPase, is a central intermediary of the epidermal growth factor receptor (EGFR) and other tyrosine kinase receptor pathways. Increased EGFR and Kras signalling is involved in colorectal carcinogenesis and tumour progression. Mutations of Kras result in the loss of its GTPase activity and thus in a constitutive activation of Kras signalling. Kras mutations are found in 30–60% of colorectal cancers. The concordance between Kras mutations in the primary tumour and related metastatic sites is high. Since mutation of Kras confers resistance to anti-EGFR-antibody therapy, it is critical to assess Kras mutational status in colorectal cancer patients. Anti-EGFR-antibody therapy improves survival in patients with metastatic colorectal cancer and wild-type Kras.